Effects of Dietary Lipid Levels on Growth Performance and Transport Stress Tolerance in Channel Catfish (Ictalurus punctatus) - Tao Teng; Dehong Zhang; Jianhua Ming; Hualiang Liang; Li Cai; Tingting Li; Xiufang Ren; Lu Zhang; Haifeng Mi (Fishes, 2026)
This study aimed to investigate the effects of dietary lipid levels on growth performance and transport stress resistance in large-sized channel catfish (Ictalurus punctatus). Four experimental diets were formulated with fat levels of 7.5% (control), 10.0%, 12.5%, and 15.0%, using soybean oil as the lipid source. Each diet was assigned to four replicate groups in a 110-day feeding trial, with fish averaging 600.61 ± 1.33 g at the start. Results showed that increasing dietary fat enhanced weight gain rate (WGR) and specific growth rate (SGR), with the 15.0% fat group achieving the best growth performance and the lowest feed conversion ratio (FCR), significantly lower than the control (p